Afghanistan - Country Procurement Assessment : Consulting Services - World Bank (Washington, DC, 2012)
Afghanistan is striving to emerge from a prolonged period of military occupation, wars and the Taliban rule. The country's security situation remains critical, especially outside of Kabul, yet the economy is stable and continues to grow. In the reconstruction process the country is receiving extensive donor support. Taking into consideration the World Bank's country assistance strategy, this report examines whether Afghanistan's Public Administration (PA) has access to the services it needs from international and national consultants under Bank and Afghan procurement rules. Both, the Bank's selection procedures and the Government of Afghanistan (GoA) policy, laws, rules of procedure, and practices are examined to determine whether they (1) lead to efficient consulting contract awards; and (2) support the development of local consulting firms. The demand and supply of international and domestic consulting services are assessed. In addition, this assessment identifies the key constraints that hamper the evolution of the domestic consulting sector. Suggestions are provided on what the GoA and the Bank could do to create an environment suitable for (1) qualified international consultants; and (2) the development of sustainable local consulting capacity necessary to help Afghanistan to implement its reform programs.